Competitive responses of an established airline to the entry of a low-cost carrier into its hub airports. (September 2017) - Chen, Ruowei
Abstract: This paper investigates the competitive responses of China Eastern to the entry of Spring Airlines into its hub airports in Shanghai. The analysis takes into account of the actual and adjacent competition for both LCCs and full-service airlines (FSAs) within an airport-pair framework. The results of the econometric analysis showed that Spring put downward pressure on the average fares of China Eastern and other FSAs. But China Eastern responded more aggressively than other FSAs to Spring's competition on routes from the same and nearby airports. Having said that, the moderate price reduction of 4%–4.9% suggests that China Eastern did not perceive Spring as a serious competitor. Such limited impacts are due to restrictions imposed by the regulator onto Spring Airlines in terms of capacity control and access to major trunk routes. Highlights: This paper takes into account of the actual and adjacent competition for both LCCs and full-service airlines within an airport-pair framework. It examines the competitive response of an established airline to the entry of a LCCs into its hub airports. LCCs have significant impacts on full service airlines' fares in China but the effects are much smaller than those found in the Western world.